2012
DOI: 10.1021/ja304348y
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Charge Transport in Films of Au Nanocrystals

Abstract: Charge transport (CT) in films of arylthiol-capped Au nanocrystals (NCs) exhibits strong substituent effects, with electron-donating substituents markedly decreasing conductivity. Films suited for measurements were obtained by ligand-exchange reactions on AuNCs grown at the water/toluene interface. Detailed analysis suggests the NCs interact with the ligands by resonance rather than inductive effects. The films were characterized by TEM, SEM, XPS, UV/vis, and AFM. CT characteristics were studied between 15 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The observed behaviour is consistent with the hopping of localized electrons from one nanocrystal to another. 21,[49][50][51] Here, the conductivity (s) is:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed behaviour is consistent with the hopping of localized electrons from one nanocrystal to another. 21,[49][50][51] Here, the conductivity (s) is:…”
Section: Resultsmentioning
confidence: 99%
“…10,19 We have shown that device quality lms of Au nanocrystals can be directly obtained from interfacial deposits using a novel transfer process. 20,21 Herein, we have been successful in obtaining interfacial deposits of Ag nanocrystals with highly reproducible transport characteristics, indicative of robust coupling between the constituent nanocrystals. Further, we show that the transport properties can be systematically varied across a large range by co-reducing Ag and Au precursors yielding Au-Ag nanoalloys.…”
Section: Introductionmentioning
confidence: 99%
“…In sequential tunneling, the electron–hole pair is separated by one particle. The Coulomb charging energy of a nanoparticle, E C , which is defined as the energy needed to add an excess electron onto an electronically neutral nanoparticle, is approximated byEnormalC=e24πεε0awhere ε is the dielectric constant and a is the particle radius. Different methods and models are reported in order to estimate the Coulomb charging energy in the array of nanoparticles but in general it can be affected by (i) the particle core size, (ii) the interparticle distance, (iii) the number of nearest neighbors, and (iv) the dielectric constant of the ligand molecules .…”
Section: Discussionmentioning
confidence: 99%
“…5 . The temperature profiles of the studied films all showed linear changes in conductivity that indicate a classical Arrhenius-type activated charge-carrier transport mechanism [ 114 ].…”
Section: Reviewmentioning
confidence: 99%
“… Conductivity as a function of the temperature in films of gold nanoparticles functionalized with thiophenol (H), with thiophenol para -substituted with nitro (NO 2 ), methyl (Me), bromine (Br), chloride (Cl), or methoxy (MeO) groups, and with triphenylphosphine (PPh 3 ). Reprinted with permission from [ 114 ], copyright 2012 American Chemical Society. …”
Section: Reviewmentioning
confidence: 99%